Phase I study of azacitidine following donor lymphocyte infusion for relapsed acute myeloid leukemia post allogeneic stem cell transplantation. (October 2016) - Ghobadi, Armin; Choi, Jaebok; Fiala, Mark A.; Fletcher, Theresa; Liu, Jingxia; Eissenberg, Linda G.; Abboud, Camille; Cashen, Amanda; Vij, Ravi; Schroeder, Mark A.; Pusic, Iskra; Stockerl-Goldstein, Keith; et al.
Highlights: Azacitidine (AzaC) on days 4, 6, 8, and 10 post DLI is safe. AzaC early post DLI can potentially prevent GVHD. The effect of AzaC post DLI on GVHD and GVL should be studied in a larger study. Abstract: Donor lymphocyte infusion (DLI) without prophylactic immunosuppression has been used for relapsed AML after allogeneic stem cell transplant (allo-SCT). However DLI is associated with an increased incidence of acute Graft vs. Host Disease (aGVHD). In mice, administration of azacitidine (AzaC) on days 4, 6, 8, and 10 post DLI increases regulatory T cell (Treg) numbers and prevents GVHD without hindering Graft vs. Leukemia (GVL). Based on these findings, we conducted a phase 1 study of AzaC post DLI for AML relapse post allo-SCT. AzaC was administered on days 4, 6, 8 and 10 post-DLI. Dose escalation was done using a 3 + 3 design with three AzaC dose levels: 30 mg/m 2 (level −1), 45 mg/m 2 (level 1) and 75 mg/m 2 (level 2). Three patients were treated in the 45 mg/m 2 dose level and 5 patients were treated in the 75 mg/m 2 dose level; no DLTs or grade 3–5 treatment related toxicities were observed. After a median follow-up of 5.2 months, no patients developed grade III–IV aGVHD and no patients died of aGVHD. Six out of 8 patients in the treatment group responded to treatment including two cytogenetic complete remissions, one hematologic complete remission, and three complete remissions with incomplete count recovery. In conclusion, administration of AzaC early post DLI is well tolerated and can potentially prevent GVHD after DLI. Further studies are required to evaluate the effect of azacitidine early post DLI on GVHD and GVL.